20. SITUATION OF THE OCCUPATIONAL ENVIRONMENT AT LAO CAI PROVINCIAL GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the occupational environment situation at Lao Cai provincial General Hospital in 2023.Subjects: Physical factors, physico-chemical factors (dust), toxic gases, occupational psychology and ergonomics of labor position.Method: A cross-sectional descriptive study was conducted on the occupational environment monitoring report of Lao Cai provincial General Hospital in 2023.Results: 100% of samples met the allowed standards for microclimate and noise measurement locations, and 55% of measurement locations had an unreliable light index. Samples measuring toxic gas and dust all meet the allowed standards. The psychological burden on healthcare workers is mostly not stressful or moderately stressful. 12/66 measurement locations measure the basic dimensions of the working position and do not meet the standards.Conclusion: Although the occupational environment at Lao Cai provincial General Hospital in 2023 was generally considered good, some aspects still needed to be improved to ensure the health and safety of healthcare workers and patients.
Keywords: Occupational environment; physical factors; dust; toxic gases; ergonomics